Technical issues and conservation conditions of medicines in the primary health care of the Brazilian Unified Health System - Costa, Ediná Alves; Araújo, Patrícia Sodré; Pereira, Marcelo Tavares; Souto, Ana Cristina; Souza, Gisélia Santana; Guerra Junior, Augusto Afonso; Acurcio, Francisco de Assis; Guibu, Ione Aquemi; Alvares, Juliana; Costa, Karen Sarmento; Karnikowski, Margô Gomes de Oliveira; Soeiro, Orlando Mario; et al. (Revista de Saúde Pública, 2017)
OBJECTIVE: To characterize the technical issues and conditions of medicines conservation in Primary Health Care of Brazilian regions, responsible for pharmacy/dispensing unit profile; environmental, storage, and dose fractioning conditions; inventory control and waste management; fire and electrical failure safety items; transportation problems; advertising regulation; and pharmacovigilance. METHODS: This article is part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços (National Survey on Access, Use and Promotion of Rational Use of Medicines – Services)–, a cross-sectional and exploratory study, of evaluative nature, consisting of an information survey within a representative sample of municipalities, stratified by Brazilian regions, which constitute the study domains, and a sample of Primary Health Care services. Pharmaceutical services (PS) were directly observed with photographic record and face-to-face interviews with those responsible for the dispensing of medicines and over the telephone with those responsible for pharmaceutical services. Data were processed with the SPSS® software version 21.RESULTS: The investigated dimensions showed relevant deficiencies and inequalities between the regions, generally more favorable in the Southeast and Midwest regions and weaker in the Northeast and North regions. We verified non-compliance with technical requirements and conditions essential to the conservation of medicines, which may interfere with the maintenance of stability and, thus, on their quality, efficacy, and safety. The regulation of advertising/promotion of medicines is still incipient and there is some progress in the structuring of mechanisms regarding pharmacovigilance. CONCLUSIONS: The sanitary situation of medicines in Brazilian Primary Health Care is alarming due to the violation of the specific sanitary legislation for dispensing establishments and due to a wide range of requirements essential to the conservation of medicines. We observed a disconnection between the efforts made in the Brazilian Unified Health System to promote access to medicines for all population and the organization and qualification of pharmaceutical services